Cross-Species Intimacies from Guide Dogs to Artificial Meat: Review of Susan McHugh, Animal Stories: Narrating across Species Lines - Armbruster, Karla (Humanimalia, 2012)
Susan McHugh, Animal Stories: Narrating across Species Lines. Minneapolis, MN:  U of Minnesota P, 2011.  280 pp. $25.00 pb.